Microwave nondestructive testing of textile and composite materials using free-space microwave measurement system / Associate Professor Dr. Jamil Salleh … [et al.] - Salleh, Jamil; Ghodgaonkar, Deepak Kumar; Wan Ahmad, Wan Yunus; Khadri, Norasimah; Mohd Tamyis, Najihah (2002)
Microwave Nondestructive Testing (MNDT) is a procedure for determining the quality or characteristics of material, part, or assembly, without permanently altering the material or its properties, by microwaves. It is used to find internal anomalies in the structure without degrading its properties. The advantages of MNDT are [1] a) Microwaves can transverse empty space, therefore coupling can be easier than using the ultrasonic methods. b) No material contamination problem occurs from the coupling material. c) Microwaves do not penetrate to any significant depth in electrical conductors, therefore they can be used as reflectors. d) Microwave can penetrate most commercial plastics and glass-reinforced structures. e) Unlike ultrasonic, microwave is not totally reflected at interfaces between solids and air. f) Information about amplitude and phase of propagating microwaves is measurable. g) Microwave can be used in hostile environment such as blast furnaces and nuclear reactor silos or bunkers to measure depth of burden, depth of grain, or depth of cooling water. h) Microwave components can be measured from metal stock, and the electronics power supplies and controllers can stand reasonably difficult environments of vibration, temperature and corrosion.